The Bankruptcy Decision and Debt Contract Renegotiations - Berkovitch, Elazar; Israel, Ronen (Review of Finance, 1998)
Abstract We consider the bankruptcy law and workout practices in the United States and model bankruptcy as a strategic decision. We analyze a firm's choice between liquidation under Chapter 7, renegotiation of the debt contract in a workout, and reorganization under Chapter 11 of the bankruptcy code. Our premise is that a financially distressed firm chooses its action in order to minimize the loss in value caused by the well-known over- and under-investment problems. We show that the firm initiates a workout when it faces under-investment, and commences Chapter 11 when it faces over-investment. Some of the results are: (i) in default, total firm value and equity value increase upon the announcement of a workout and decrease upon the announcement of Chapter 11; (ii) firms with shorter maturity of debt are more likely to reorganize in a workout; (iii) among the firms that renegotiate their debt contract, the proportion of firms entering Chapter 11 is higher for firms in mature industries than for firms in growth industries.